Економіко – математична модель ринку плодово – ягідної продукції Півдня України: прогноз дії системи - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2020)
UK: Визначено важливість застосування методів математичного моделювання під час прогнозування розвитку економічних явищ та систем. Розглянуто результати сформованої моделі системи "ринок плодово-ягідної системи Півдня України". Встановлено цільові фактори та важелі, що спричиняють зміни. У загальному вигляді складено рівняння криволінійної залежності системи. На підставі критерію Фішера оцінено та підтверджено доцільність врахування факторів та їхньої сили зв'язку під час узастосування у сценарному аналізі. За умов фіксованих факторів побудовано поверхні найбільш сприятливих сценаріїв розвитку ринку продукції як економічної системи. Визначено сукупність важелів, які найбільш позитивно сприяють розвитку системи. Окреслено подальші напрями функціонування ринку продукції, як системи за умов врахування дії виділених важелів. EN: The market for fruit and berry products is a complex economic system. The effect of its components is influenced by constantly changing variables. Therefore, the need to apply mathematical modeling methods in the development of the forecast of the development of economic phenomena and systems is urgent. In the process of modeling the market of fruit and berry products, the following methods are used: mathematical statistics and econometrics (correlation and regression analysis); optimal decision-making (mathematical programming, operations research, analysis of event scenarios). A model of the system is constructed using mathematical methods: "market of fruit and berry products in the South of Ukraine". The main target factors are established: producers of products, processing and procurement enterprises, the size of export-import operations. In the process of calculating the market size, the levers that affect the system are taken into account. The levers are determined based on scenario analysis and include: product quality, scientific and technical progress, investment, state support for the industry. In General, the equation of the system's curvilinear dependence is compiled. Based on the Fischer criterion, the strength of the connection of factors was evaluated and confirmed. Graphically constructed surfaces of the most favorable scenarios for the development of the product market. The forecast of changes in the market as a system under the action of levers is obtained. Five scenarios were considered. It is determined that the best scenarios are those where the development of the fruit and berry market is influenced by the quality of products, scientific and technical progress and state support for the industry. The results of the study are the basis for further analysis of the impact of certain levers, as well as the development of separate proposals for each of them. With targeted impact and a systematic approach to the implementation of proposals, the market of fruit and berry products will have positive changes. Taking into account forecasts will make it possible to increase the capacity of the product market in the domestic and foreign markets.
Экономико-математическая модель рынка плодово-ягодной продукции Юга Украины: прогноз действия системы
Economic-mathematical market model of fruit production in the South of Ukraine: forecast of the system
Keywords: економіко-математична модель; прогноз; сценарій; ринок; цільові фактори; экономико-математическая модель; сценарий; рынок; целевые факторы; economic and mathematical model; forecast; scenario; market; target factors